The Effect of Implementing Project Based Learning Assisted by Manipulative Learning Media on Elementary School Students Understanding (AJER: Advanced Journal of Education and Religion, 2024)
This research aims to determine if the Problem Based Learning (PBL) learning model assisted by real media affects student learning outcomes at MI Islamiyah Kedungmegarih. The lack of teacher creativity in using innovative learning models and the suitability of the media with the material being delivered so that learning outcomes are not optimal. To overcome these problems, there are recommendations for alternative actions that are effective and innovative so that students obtain maximum learning outcomes. This study uses a quantitative approach. The design used is quasi-experimental. The research design used a pretest and posttest with a non-equivalent control group design. To answer the research hypothesis, the independent sample T-test formula is used. Based on the results of this study, this statement was proven by the average post-test results in both classes, namely, in the experimental category, it was 82.80 and in the control class, it was 70.80. In addition, based on the results of which is more significant than 5.42 compared to of 1.72, it means that Is rejected and is accepted, meaning that there is a significant influence on student learning outcomes than without using the Problem Based Learning (PBL) learning model assisted by concrete media in improving results student learning on material changes in the form of objects in class VA MI Islamiyah Kedungmegarih.